A arte através da música na vida de crianças e adolescentes, filhos(as) de (i)migrantes: aproximações de três programas sociais localizados em São Paulo, Coimbra e Amsterdam que trabalham com essa demanda - Silva, Fabiana Aparecida da (2020)
This thesis presents the PhD research with children and adolescents, children of (i) migrants, who have daily contact with art through music in the Social Programs of Musical Education: Guri Santa Marcelina, in São Paulo, Brazil. Generation Orchestra in Coimbra and Leerorkest in Amsterdam. These three programs show the potential of music as an instrument for bringing children and adolescents closer, as this experience enriches the sensitivity of these subjects, contributing to their development and socialization in states / countries with different customs and cultures - the main objective of this thesis. The theoretical framework is based on historical materialism regarding art, work and (i) migration, main categories of research analysis. Quantitative data from research institutions were also used. In the field research, the qualitative research was applied through participant observation and oral history, with the record of the speeches of the subjects who serve these children, adolescents and families. The choice of oral history was essential because it works with the individual's memories, interacting with what happens at the intersection of the individual with the social in the present tense. Finally, the main actors in the research of children and adolescents from three Social Programs in different countries were brought through the exchange of correspondence between them